Effect of Guava Powder Addition on Epigallocatechin Gallate (EGCG) Content of Green Tea and Its Antioxidant Activity - Hanifah Ridha Rabbani; Djoko Agus Purwanto; Isnaeni Isnaeni (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2019)
Background: Tea (Camelia sinensis) contains polyphenols including epigallocatechin gallate (EGCG) which is acknowledged to have strong antioxidant properties. However, its stability is strongly influenced by environment. In a neutral and alkaline environment, EGCG could undergo degradation and lose its antioxidant property. There are some researches about the effect of combination of green tea and other plants to their antioxidant capacity. Objective: The research aimed to investigate the effect of guava addition to EGCG content of green tea and their antioxidant activity. Methods: The concentration of EGCG was determined by chromatographic analysis using TLC scanner, meanwhile the antioxidant activity was evaluated by its ability in scavenging 2,2-diphenyl-1-picrylhydrazyl (DPPH) using UV-Vis Spectrophotometer. Results: Among all the samples, formula 4 (2 parts of green tea and 3 parts of guava) gave the highest EGCG content (39.03 ± 3.65 mg/g). This was 37.5% higher than the control sample (28.39 ± 2.45 mg/g). Formula 4 also had the best antioxidant activity with IC50 of 1917.32±1.75 ppm, 19% lower than control sample (2356.46 ± 3.16 ppm). Conclusion: The addition of guava powder significantly increased the amount of EGCG in green tea extracts and their antioxidant activity.